Cost of healthcare services in patients with chronic rhinosinusitis from the public hospital perspective: a retrospective prevalence-based costing approach - Trung Quang Vo (GarVal Editorial Ltda., 2019)
Context: Chronic rhinosinusitis (CRS) is a high-incidence health concern and therefore cause a high economic burden. Aim: To evaluate the direct medical cost in CRS treatment. The findings of this research promised as a real evidence on decision-making. Methods: This study was designed as a cost analysis study based on prevalent rate. The electronic database of a public hospital was used to find out the demographic characteristics and costs associated with CRS from healthcare provider (hospital), patient and third-party (health insurance) perspective. Data on 4,894 individuals with CRS treated at the Ear-Nose-Throat Hospital collected from 2015 to 2017 were analyzed. Results: The age of majority was between 33 and 55 years, and the number of patients with insurance increased annually. About 35% of participants came from Ho Chi Minh City, and the median length of stay was 6 days. The direct medical costs per year per episode were 700.13 USD with health insurance and 1066.26 USD without health insurance. Treatment costs were found to be significantly different among years. The factors that directly influenced medical costs were gender, health insurance, and type of CRS. Conclusions: This analysis states for the first time the specific costs for CRS, which would provide public health professionals with estimated the economic burden of CRS. The study provides a baseline treatment cost of CRS that can be used by future studies for comparison.